Fanning behavior of stingless bee, Heterotrigona itama (COCKERELL, 1918) (HYMENOPTERA: APIDAE) - Zulidzham Mohd Sani; Fahimee Jaapar; Salmah Yaakop
The increase of temperature shows a negative impact on the behavior of the insects live in colonies, including the stingless bees. The stingless bees employ the fanning behavior as the best method to remove excess heat within colonies. The objective of this study was to investigate the fanning behavior of the Heterotrigona itama (Cockerell) in relation to regulate inner temperature and relative humidity. This study was conducted from January 2023 to May 2023 using three colonies. The fanning behavior of H. itama has been observed from 0800H until 1700H for 5 minutes per hour per 3 days for 5 months with camera recorder. There were significant differences between time and fanning behavior (F9,449 = 34.96, P>0.005) from 0800H to 1700H. In addition, the frequency of fanning behavior increased when the temperature hit on 28ºC±SD and stop when the temperature below 27ºC±SD and showed a significant difference (F70,449 = 42.59, P>0.005). Furthermore, changes of humidity also stimulate the fanning behavior of H. itama and showed a significant different (F41,449 = 36.83, P>0.05). Besides that, the fanning behavior started with aggregation of workers at the entrance and the leader site at the top of the entrance to stimulate other workers to fan the hives according to the changes of the temperature. The fanning behavior occurred during the hot season to reduce the temperature inside the colony, while stabilizing the humidity inside the colony during the raining seasons.